History of Warfare, Volume 48 : British popular culture and the First World War - Meyer, Jessica (History of warfare, 2008)
Much of the scholarship examining British culture of the First World War focusses on the 'high' culture of a limited number of novels, memoirs, plays and works of art, and the cultural reaction to them. This collection, by focussing on the cultural forms produced by and for a much wider range of social groups, including veterans, women, museum visitors and film goers, greatly expands the debate over how the war was represented by participants and the meanings ascribed to it in cultural production. Showcasing the work of both established academics and emerging scholars of the field ...